Performance Analysis of Sustainable Investments in the Brazilian Stock Market: A Study About the Corporate Sustainability Index (ISE) - Arias Fogliano de Souza Cunha, Felipe; Samanez, Carlos P. 1953-2016 (2013)
In this article, we studied the Corporate Sustainability Index (ISE) of the Brazilian Mercantile, Futures and Stock Exchange (BM&FBOVESPA), with the main objective of analyzing the performance of sustainable investments in the Brazilian stock market, during the period from December 2005 to December 2010. To achieve this aim, we characterized ISE portfolios and we compared its performance with the IBOVESPA (representing the market portfolio) and other BM&FBOVESPA sectoral indices. In the performance comparison, we used level of liquidity, return and risk indicators, as well as the following measures: Sharpe, Treynor, Sortino, and Omega. Our results show that although sustainable investments have presented some interesting characteristics, such as increasing liquidity and low diversifiable risk, they did not achieve satisfactory financial performance in the analysis period. This indicates that the constraints imposed by this type of investment in capital allocation in Brazil may be harming their return and risk attractiveness.
Keywords: sustainable investment; Socially Responsible Investment; Portfolio performance analysis; Corporate Sustainability Index (ISE); Brazilian stock market